The MicroRNA MiR-29c Alleviates Renal Fibrosis via TPM1-Mediated Suppression of the Wnt/β-Catenin Pathway - Huang, Huiya; Huang, Xiaozhong; Luo, Shengnan; Zhang, Huidi; Hu, Feifei; Chen, Ruyi; Huang, Chaoxing; Su, Zhen (Frontiers in Physiology, 2020)
Purpose This study aimed to evaluate the mechanism by which miR-29c expression in fibroblasts regulates renal interstitial fibrosis. Methods We stimulated NRK-49F cells with TGF-β1 to mimic the effects of fibrosis in vitro, while unilateral ureteral obstruction (UUO) was performed to obstruct the mid-ureter in mice. MiR-29c mimic or miR-29c inhibitor was used to mediate genes expressions in vitro. The recombinant adeno associated virus (rAAV) vectors carrying a FSP1 promoter that encodes miR-29c precursor or miR-29c inhibitor was used to mediate genes expressions in vivo, and a flank incision was made to expose the left kidney of each animal. Results In the present study, TGF-β1 was demonstrated to regulate miR-29c expression through Wnt/β-catenin signaling. In contrast, miR-29c appears to inhibit the Wnt/β-catenin pathway by suppressing TPM1 expression. As suggested by this feedback mechanism, miR-29c may be a key fibrosis-related microRNA expressed by fibroblasts in TGF-β1/Wnt/β-catenin-driven renal fibrosis, and manipulation of miR-29c action may accordingly offer a potential therapeutic pathway for renal fibrosis treatment. Conclusion MiR-29c expression was downregulated in UUO mouse kidneys as well as TGF-β1-treated NRK-49F cells, which thus inhibits myofibroblast formation via targeting of TPM1. Additionally, the production of extracellular matrix (ECM) in renal fibroblasts appears to be controlled by the reciprocal regulation of miR-29c action and the Wnt/β-catenin pathway.